The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/adma.201304546
|View full text |Cite
|
Sign up to set email alerts
|

Scale Effects of Low‐Dimensional Relaxor Ferroelectric Single Crystals and Their Application in Novel Pyroelectric Infrared Detectors

Abstract: Scaling effects of low-dimensional relaxor ferroelectric single crystals have induced large delocalization of domain switching, leading to a dramatic increase in pyro-electric performances by 2-5.5 times, and promoting the detectivity of fabricated pyroelectric detectors to an international leading level of 2.21 × 10(9) cmHz(1/2) /W at 10 Hz, 4 times higher than that of commercial LiTaO3 -based detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Mn‐doped R binary crystals exhibit higher pyroelectric properties than conventional pyroelectric materials, such as lithium tantalate (LiTaO 3 ) single crystal and lead zirconate titanate (PZT) ceramics . As a consequence, the detectivity of IR detectors based on the binary crystals are four times larger than that of commercially available ones based on LiTaO 3 single crystals . Recently, it was found that [001]‐oriented Mn‐doped tetragonal 0.29Pb(In 1/2 Nb 1/2 )O 3 ‐0.29Pb(Mg 1/3 Nb 2/3 )O 3 ‐0.42PbTiO 3 (Mn‐0.29PIN‐0.29PMN‐0.42PT) ternary single crystals exhibited not only comparable FOMs, but also better thermal stability over a wider temperature range due to its higher T C compared with binary ones .…”
Section: Introductionmentioning
confidence: 99%
“…Mn‐doped R binary crystals exhibit higher pyroelectric properties than conventional pyroelectric materials, such as lithium tantalate (LiTaO 3 ) single crystal and lead zirconate titanate (PZT) ceramics . As a consequence, the detectivity of IR detectors based on the binary crystals are four times larger than that of commercially available ones based on LiTaO 3 single crystals . Recently, it was found that [001]‐oriented Mn‐doped tetragonal 0.29Pb(In 1/2 Nb 1/2 )O 3 ‐0.29Pb(Mg 1/3 Nb 2/3 )O 3 ‐0.42PbTiO 3 (Mn‐0.29PIN‐0.29PMN‐0.42PT) ternary single crystals exhibited not only comparable FOMs, but also better thermal stability over a wider temperature range due to its higher T C compared with binary ones .…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, infrared sensors made of ferroelectric materials exhibit great advantages of uncooled operation, high sensitivity, broad spectral response range and low cost compared with photon detectors and are widely used in alarms, thermal imaging and intruder imaging [4][5][6]. Thin film ferroelectric infrared detectors and focal plan arrays are expected to yield better sensitivities and faster response than equivalent ceramics and bulk single crystals, and can be deposited directly on silicon readout integrated circuitry [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The pyroelectric performance can be characterized by three figures of merit (FOMs), that is, FOMs for current responsivity F i = p/C v , voltage responsivity F v = p /( C v ε 0 ε r ) and detectivity F d = p/[C v (ε 0 ε r tan δ) 1/2 ], where p is the pyroelectric charge coefficient, C v the volume specific heat, ε 0 the vacuum dielectric constant, ε r the relative dielectric constant and tanδ the dielectric loss tangent . Relaxor ferroelectric single crystals represented by Pb(Mg 1/3 Nb 2/3 )O 3 ‐PbTiO 3 (PMNT) are considered as one of the most promising next‐generation pyroelectric materials due to their high ultrahigh pyroelectric coefficient, low specific heat, adaptable relative dielectric constant, and relatively low dielectric loss …”
Section: Introductionmentioning
confidence: 99%
“…4 Relaxor ferroelectric single crystals represented by Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMNT) are considered as one of the most promising next-generation pyroelectric materials due to their high ultrahigh pyroelectric coefficient, low specific heat, adaptable relative dielectric constant, and relatively low dielectric loss. [5][6][7][8] Tang et al found that the rhombohedral 0.74Pb(Mg 1/3 Nb 2/3 ) O 3 -0.26PbTiO 3 (PMNT(74/26)) crystal is the optimum composition, which exhibits the best pyroelectric performance when poled along [111] direction, with P = 15.3 × 10 −4 C m −2 K −1 , ε r = 643, tanδ = 0.0028, F i = 6.1 × 10 −10 m V −1 , F v = 0.11 m 2 C −1 and F d = 15.3 × 10 −5 Pa −1/2 . 9,10 Further investigation carried out by Liu et al showed that the doping of Mn can enhance the pyroelectric response and decline dielectric loss, and the F d value of the Mn-doped PMNT(74/26) crystal can reach to 40.2 × 10 −5 Pa −1/2 , nearly three times of the undoped one.…”
Section: Introductionmentioning
confidence: 99%